Measuring Entrepreneurial Intentions: Does Entrepreneurial Orientation Moderate Perceived Behavioral Control? - Putri, Dominica Prima Kurnia Kharismatika; Radianto, Wirawan Endro Dwi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines the effect of Perceived Behavioral Control (PBC) on Entrepreneurial Intention (EI), with Entrepreneurial Orientation (EO) as a moderating variable among Master of Management students at Ciputra University. Using a quantitative approach and SEM-PLS analysis of 172 respondents, the findings show that PBC positively and significantly influences EI, indicating that stronger behavioral control enhances entrepreneurial intention. However, EO does not moderate the relationship between PBC and EI, suggesting that individuals with high PBC rely more on personal confidence than entrepreneurial orientation traits. This study contributes to the Theory of Planned Behavior by clarifying the central role of behavioral control in entrepreneurial intention formation. Practically, the findings suggest that entrepreneurship programs should strengthen students’ self-efficacy, confidence, and adaptive capabilities, particularly among Gen Z students. Apparently, compressing academic ego into 150 words is harder than structural equation modeling.